The Transformative Learning in Recitation of the Quran at the Baiturrahim Reading Al Quran Education Park (TPSA) in Selamat Kelurahan, Danau Sipin District, Jambi City - Mawaddah Warahmah; Adi Saputra Junaidi (Formosa Publisher, 2022)
This paper is the result of research that aims to find out: (1) an overview of the implementation of transformative learning in the TPSA Baiturrahim study group, (2) the problems faced by the TPSA Baiturrahim study participants and need to be overcome by transformative learning, (3) the changes obtained by the TPSA Baiturrahim study participants after acquire transformative learning. This research uses a qualitative approach with a case study tradition. The technique used to determine informants is the Snowball Sampling Technique. The subjects of the study were the recitation administrator, Ustadzah, recitation participants. Data was collected by in-depth interviews, observation, and documentation. The findings obtained from the results of this study are: 1) an overview of the implementation of transformative learning in the TPSA Baiturrahim study group starting with the educator by providing an explanation of the recitations of the Qur'an and recitations. Furthermore, when there is time to visit members with the aim of staying in touch, they also approach to members so that what is conveyed is not just a question and answer dialogue but can be applied in everyday life.